2017
DOI: 10.1200/jco.2016.70.7349
|View full text |Cite
|
Sign up to set email alerts
|

Dose-Reduced Versus Standard Conditioning Followed by Allogeneic Stem-Cell Transplantation for Patients With Myelodysplastic Syndrome: A Prospective Randomized Phase III Study of the EBMT (RICMAC Trial)

Abstract: To compare a reduced-intensity conditioning regimen (RIC) with a myeloablative conditioning regimen (MAC) before allogeneic transplantation in patients with myelodysplastic syndrome (MDS) within a randomized trial. Patients and MethodsWithin the European Society of Blood and Marrow Transplantation, we conducted a prospective, multicenter, open-label, randomized phase III trial that compared a busulfan-based RIC with MAC in patients with MDS or secondary acute myeloid leukemia. A total of 129 patients were enro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
165
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 209 publications
(180 citation statements)
references
References 15 publications
11
165
3
1
Order By: Relevance
“…When the analysis was extended to smaller population of patients allografted using a RIC regimen, although statistical power was lost broadly similar disease-and transplant-specific factors determining relapse kinetics were identified, although of interest the utilization of in vivo TCD emerged as a significant risk factor in this distinct setting. Of interest, the use of a RIC regimen was not associated with an increased risk of disease relapse which is consistent with two recent prospective randomized trials but at variance with the findings of a recently reported US CTN study [15][16][17]. Taken together, these data suggest the existence of a complex interaction between leukaemia-and transplant-specific factors in the maintenance of disease remission post-transplant and identify potential manipulable pathways at different stages post-transplant.…”
Section: Discussionsupporting
confidence: 86%
“…When the analysis was extended to smaller population of patients allografted using a RIC regimen, although statistical power was lost broadly similar disease-and transplant-specific factors determining relapse kinetics were identified, although of interest the utilization of in vivo TCD emerged as a significant risk factor in this distinct setting. Of interest, the use of a RIC regimen was not associated with an increased risk of disease relapse which is consistent with two recent prospective randomized trials but at variance with the findings of a recently reported US CTN study [15][16][17]. Taken together, these data suggest the existence of a complex interaction between leukaemia-and transplant-specific factors in the maintenance of disease remission post-transplant and identify potential manipulable pathways at different stages post-transplant.…”
Section: Discussionsupporting
confidence: 86%
“…Regarding the prognostic impact of der(1;7) there are conflicting data showing dismal, intermediate, and favorable prognosis of der(1;7), precluding reliable therapy allocation, in particular with regard to proceeding to allogeneic hematopoietic stem cell transplantation (HSCT) or not. Allogeneic HSCT is increasingly used as curative treatment option in MDS . Considering this therapeutic approach, we set out to investigate the impact of isolated der(1;7) on disease characteristics and prognosis in a well‐characterized cohort of patients with MDS and closely related myeloid disorders such as oligoblastic sAML and chronic myelomonocytic leukemia (CMML).…”
Section: Introductionmentioning
confidence: 99%
“…Allogeneic HSCT is increasingly used as curative treatment option in MDS. 8,9 Considering this therapeutic approach, we set out to investigate the impact of isolated der(1;7) on disease characteristics and prognosis in a wellcharacterized cohort of patients with MDS and closely related myeloid disorders such as oligoblastic sAML and chronic myelomonocytic leukemia (CMML). Furthermore, the structure and the breakpoints of this chromosomal aberration were analyzed in detail.…”
mentioning
confidence: 99%
“…sAML has been reported to be associated with worse outcome compared to de novo AML in some studies (Smith et al , ; Koh et al , ; Miesner et al , ) and poor outcome may be related to poor cytogenetics, more comorbidities and older age in those patients (Mesa et al , ). For sAML, allogeneic haematopoietic stem cell transplantation (allo‐HSCT) is a curable treatment approach in transplant‐eligible patients (Witherspoon & Deeg, ; Lussana et al , ; Symeonidis et al , ; Kroger et al , ). A recent epidemiological study suggested different outcomes in the non‐transplant setting if sAML was transformed from MDS or other myeloid malignancies such as CMML or MPN (Granfeldt Ostgard et al , ).…”
mentioning
confidence: 99%